Correlation of optic nerve sheath diameter with intracranial pressure monitoring in patients with severe traumatic brain injury - Sahoo, Siddhartha Shankar; Agrawal, Deepak (Indian Journal of Neurotrauma, 2013)
To assess the feasibility and reliability of using optic nerve sheath diameter (ONSD) as an objective measure of intracranial pressure (ICP) in patients of severe head injury.This prospective study was carried out in Neurosurgery ICU over a 3-month period (April–June 2012). All patients with severe traumatic brain injury (admission GCS ≤8) who had ICP monitoring using Codman® intraparenchymal transducer had serial bedside ONSD measurements taken by a single neurosurgeon using a 7.5 MHz linear probe on the same ultrasound machine (Sonosite Micromaxx®) were enrolled in the study. Patients with significant ocular trauma to either eye were excluded.A total of 20 patients were enrolled during the study period. The mean age was 27 years (range 2–43 years) with M:F ratio of 3:1 and mean GCS of 6 (range 4–8). The mean ONSD in patients with ICP >20 was 6.6 ± 0.45 mm as compared to 5.9 ± 0.57 mm in patients with ICP <20 (p = 0.028). The Pearson Correlation Coefficient between ONSD (average of both eyes) and ICP was 0.499 (p = 0.041). A cutoff of 6.3 mm detected ICP >20 mmHg with 100% sensitivity and 72.7% specificity.ONSD is a technically simple, non-invasive method of assessing ICP and correlates well with actual ICP in patients of severe traumatic brain injury. A cutoff of 6.3 mm can be used to plan therapeutic interventions when ICP monitoring is unavailable or contraindicated.
Keywords: Intracranial pressure; Ultrasound; TBI; Optic nerve sheath diameter; Severe traumatic brain injury